2019
DOI: 10.1016/j.radcr.2019.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of symptomatic intralobar pulmonary sequestration – A minimally invasive treatment option

Abstract: The growing field of interventional radiology provides a number of treatment options alternative to previous relied upon invasive surgeries. Pulmonary sequestration is a condition where the option of interventional radiology is particularly promising. Described is a 41-year-old male who elected alternative treatment for his symptomatic intralobar sequestration in order to avoid associated complications of extensive surgery. Specifically, this case reports a successful cure utilizing minimally invasive emboliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Therefore, interventional embolization with a small traumatic area and rapid prognostic recovery, and placement of a spring coil were chosen. Healy et al reported a patient successfully cured by this method in 2019, confirming the superiority of this method, 11,12 and right heart contrast echocardiography played an important role in the selection of the procedure.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, interventional embolization with a small traumatic area and rapid prognostic recovery, and placement of a spring coil were chosen. Healy et al reported a patient successfully cured by this method in 2019, confirming the superiority of this method, 11,12 and right heart contrast echocardiography played an important role in the selection of the procedure.…”
Section: Discussionmentioning
confidence: 77%
“…Currently, VATS has become the main surgical technique with the advantages of being minimally invasive, accurate and rapid recovery. Some studies21–23 reported the application of transcatheter arterial embolization in the treatment of PS. This method is not widely practiced and has many complications (especially ionizing radiation).…”
Section: Discussionmentioning
confidence: 99%
“…La embolización exitosa como tratamiento definitivo ha sido reportada con el uso de partículas de polivinilo-alcohol (PVA) 11 , el empleo combinado de PVA con micro coils, empleo exclusivo de micro coils, gel foam para oclusión de los vasos distales y posterior oclusión del tronco nutricio con micro coils, uso de dispositivo Amplatzer y exclusión endovascular con colocación de stent-graft 9,12,13 , siendo el empleo de micro coils el material mayormente escogido en los casos reportados 14 .…”
Section: Discussionunclassified